Pricing of Guarantee Returns on Defined Contribution [DC] PEnsions Schemes in Ghana. - Addo, R.K. (University of Ghana, 2017)
Ghana since the implementation of the 3-tier pension schemes, has no guarantees on the tier-2 DC, which brings the problem about the safeness of contributors’ retirement funds. Analysis of the tier-1 and the tier-2 schemes show that the returns in both cases at retirement, [thus the value of annuity of tier-1 at retirement and the value of tier-2 at retirement] by ratio analysis is almost the same. There are some instances where the tier-2 is half of the tier-1, or even more. Which clearly brings in mind the need of such value to be guaranteed, even if not all, but some minimum returns underlining the fact that the risk of investment on tier-2 are all absorbed by the contributor. Pension guarantees in general would appear to be inexpensive. Guarantees of pension income generated by capital guarantee is low, and may result in the individual falling back on the state, because their pension funds are less than any minimum income guarantee. However, other forms of guarantee such as 5% rate provides a safe net for the retiree with cost comparable with the charges. There is the need for a regulators and policy makers to design guarantees on the mandatory DC scheme, at least a capital guarantee
Keywords: pension fund; guarantee; contribution; simulation